1970
DOI: 10.1099/00221287-63-3-325
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Growth-limiting Substrate and Medium NaCl Concentration on the Synthesis of Magnesium-binding Sites in the Walls of Bacillus subtilis var. niger

Abstract: A comparative study has been made of the influence of growth environment on the properties of the walls of Bacillus subtilis var. niger organisms, particularly with respect to ability to bind magnesium ions. The medium NaCl concentration and the nature of the growth-limiting substrate, in chemostat cultures, both affected markedly the subsequent affinity and capacity of the bacterial walls for Mg2+ adsorption. These changes correlated with differences in the phosphate content of the walls, which in turn relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…There i.s evidence that magnesium-limited Bacilllus subtilis cells excrete compounds that bind magnesium, thereby improving their ability to compete with other organisms for growth-limiting amounts of magnesium (82). Similarly, cell walls of magnesium-limited cells of this organism showed an increased Mg 2+ binding affinity over magnesium-sufficient cells (83). The latter process indicates that certain organisms may respond to magnesium limitation by synthesizing binding sites in the cell wall at which these cations may be concentrated prior to their translocation.…”
Section: Magnesium Limitationmentioning
confidence: 99%
“…There i.s evidence that magnesium-limited Bacilllus subtilis cells excrete compounds that bind magnesium, thereby improving their ability to compete with other organisms for growth-limiting amounts of magnesium (82). Similarly, cell walls of magnesium-limited cells of this organism showed an increased Mg 2+ binding affinity over magnesium-sufficient cells (83). The latter process indicates that certain organisms may respond to magnesium limitation by synthesizing binding sites in the cell wall at which these cations may be concentrated prior to their translocation.…”
Section: Magnesium Limitationmentioning
confidence: 99%
“…The affinity of Mg for sublethally-injured cells was measured by washing with NaCl (Tempest & Strange, 1966;Meers & Tempest, 1970;Tempest, Dicks & Meers, 1967). The heat-injured cells were allowed to repair as described above and sampled hourly.…”
Section: Afinity Of Mg For Staphylococcus Aureus Cellsmentioning
confidence: 99%
“…I b). Ultimately the pool glutamate (and potassium) contents did increase (Table 9, but the slowness of this change suggested that it had resulted more from some progressive change in cell structure (for example, in their wall content and composition; see Meers & Tempest, 1969) rather than in the functioning of the organisms. It is clear that, in growing bacteria, some correlation exists between their contents of potassium and free glutamate (see Tables I to 6 and the papers of Tempest & Dicks, 1967;Tempest & Meers, 1968).…”
Section: Tempest J L Meers and C M B R O W Nmentioning
confidence: 99%